(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2020)
The nature of work in modern society is changing rapidly, and competition in the job market is getting more intense. This requires competence from workers and demands them to update their knowledge, skills, and attitudes in order to remain productive and retain their attractiveness in the job market. On the other hand, skilful employees are a company’s most important competitive assets, and so it is worth to up- skill the employees by providing training at regular intervals on process and also on governing themselves from workplace illness. Thus the present study is an attempt to create awareness on ergonomics that impact employee performance. The significance and prominent role of ergonomics is reviewed by discussing its association with other scientific disciplines and by ascribing types of ergonomics and its principles and applications towards employee wellness.